Persuasive Communication of the TikTok Account @byrafikawu in Attracting Consumers) - Oktavia, Maria Ulfah; Sari, Sapta; Endang SM , Anis (Universitas Dehasen Bengkulu, 2025)
The rapid development of information and communication technology has transformed the way individuals interact, especially through social media platforms like TikTok. This study aims to explore the persuasive communication strategies employed by the TikTok account @byrafikawu in attracting consumers. Utilizing the Elaboration Likelihood Model (ELM) as a theoretical framework, this research investigates how both central and peripheral routes of persuasion are utilized in the content and live streaming activities of the account. The study adopts a qualitative approach with data collected through observation, in-depth interviews, and documentation. Findings reveal that the central route is demonstrated through detailed product descriptions, clear and rational messaging, and consumer education regarding product quality, benefits, and usage. Meanwhile, the peripheral route involves the use of aesthetic visual elements, influencer endorsements, humor, engaging storytelling (soft selling), and interactive features such as live streaming. These elements serve to evoke emotional connections and enhance consumer trust, especially among users who process messages less critically. The account owner also applies SEO strategies to increase discoverability and ensures message clarity by tailoring communication styles to the target audience. The persuasive communication observed in @byrafikawu not only influences purchase decisions but also contributes to long-term customer engagement and loyalty. This study contributes to the growing literature on digital marketing communication by highlighting the importance of integrated persuasive strategies on social media platforms, particularly TikTok, in influencing consumer behavior in the e-commerce context.